2009
DOI: 10.1159/000230713
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones as Therapy for Endometriosis: A Case Series

Abstract: Background: Current medical therapies for endometriosis result in delayed conception and have not been shown to provide any fertile benefit subsequent to treatment. Thiazolidinediones (TZDs) do not impede conception and have been shown to reduce endometriotic lesions in animal models; however, no studies have been performed in humans. The aim of this study was to provide preliminary data about the effectiveness of a TZD in treating endometriosis-related pain. Methods: Case series of women with endometriosis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 49 publications
(27 reference statements)
0
23
0
1
Order By: Relevance
“…In endometriosis treatment, an overall beneficial effect has been reported after administration of rosiglitazone in a reduced number of patients with endometriosis, including ameliorating endometriosis symptoms and pain (45). It is noteworthy that rosiglitazone not only does not impede ovulation (45) but also has been reported to help restore spontaneous ovulation (46), an improvement over current medical therapies for endometriosis (45).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In endometriosis treatment, an overall beneficial effect has been reported after administration of rosiglitazone in a reduced number of patients with endometriosis, including ameliorating endometriosis symptoms and pain (45). It is noteworthy that rosiglitazone not only does not impede ovulation (45) but also has been reported to help restore spontaneous ovulation (46), an improvement over current medical therapies for endometriosis (45).…”
Section: Figurementioning
confidence: 99%
“…It is noteworthy that rosiglitazone not only does not impede ovulation (45) but also has been reported to help restore spontaneous ovulation (46), an improvement over current medical therapies for endometriosis (45). In addition, it has been reported that rosiglitazone does not cause any alteration to the mouse fetus when administered during pregnancy (25).…”
Section: Figurementioning
confidence: 99%
“…Hence, the therapeutic spectrum of TZDs may be extended to include an additional patient population, women with endometriosis. However, to date only case series have reported benefits of TZDs in the treatment of endometriosis [50].…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%
“…PPARG activators such as pioglitazone and TZD-R are widely used in patients with DM 2 [79]. Besides their role in targeting metabolism, pleitropic functions such as antiproliferative and anti-inflammatory effects have been described [50]. In contrast, TZDs can promote weight gain and peripheral edema and increase the risk of myocardial ischemia (especially TZD-R versus placebo) [80,81].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…The size of surgically induced endometriotic lesions was reduced by ciglitazone in rats (2) and by rosiglitazone in baboons (3), whereas pioglitazone prevented their establishment in baboon (4) and inhibited postsurgical adhesion in a chimeric model of human endometrial biopsies in immunocompromised mice (5). Rosiglitazone has also reduced pain reported in a human case series (6). Although TZDs are available for clinical use they have also been plagued by side effects.…”
mentioning
confidence: 99%